Development of 18F-Labeled Bispyridyl Tetrazines for In Vivo Pretargeted PET Imaging - Rocío García-Vázquez; Jesper Tranekjær Jørgensen; Klas Erik Bratteby; Vladimir Shalgunov; Lars Hvass; Matthias M. Herth; Andreas Kjær; Umberto Maria Battisti (Pharmaceuticals, 2022)
Pretargeted PET imaging is an emerging and fast-developing method to monitor immuno-oncology strategies. Currently, tetrazine ligation is considered the most promising bioorthogonal reaction for pretargeting in vivo. Recently, we have developed a method to 18F-label ultrareactive tetrazines by copper-mediated fluorinations. However, bispyridyl tetrazines—one of the most promising structures for in vivo pretargeted applications—were inaccessible using this strategy. We believed that our successful efforts to 18F-label H-tetrazines using low basic labeling conditions could also be used to label bispyridyl tetrazines via aliphatic nucleophilic substitution. Here, we report the first direct 18F-labeling of bispyridyl tetrazines, their optimization for in vivo use, as well as their successful application in pretargeted PET imaging. This strategy resulted in the design of [18F]45, which could be labeled in a satisfactorily radiochemical yield (RCY = 16%), molar activity (Am = 57 GBq/µmol), and high radiochemical purity (RCP > 98%). The [18F]45 displayed a target-to-background ratio comparable to previously successfully applied tracers for pretargeted imaging. This study showed that bispyridyl tetrazines can be developed into pretargeted imaging agents. These structures allow an easy chemical modification of 18F-labeled tetrazines, paving the road toward highly functionalized pretargeting tools. Moreover, bispyridyl tetrazines led to near-instant drug release of iTCO-tetrazine-based ‘click-to-release’ reactions. Consequently, 18F-labeled bispyridyl tetrazines bear the possibility to quantify such release in vivo in the future.